Deceased donor skin banking for making use of cadaveric skin as a temporary coverage: A life saving option to the patients with extensive burn injuries - Abhishek Adhya; Arindam Sarkar; Monoranjan Sow; Soumya Gayen (Annals of Medical Science and Research)
Background: In India, xenografts are not available yet and biosynthetic skin substitutes are unaffordable to most of people. Deceased donor skin could be a lifesaving option for the victims with extensive burn injuries. The first deceased donor skin bank of eastern India was established at the Department of Plastic Surgery of a tertiary burn referral center, Kolkata on 22nd April 2013 for processing, storage, and utilization of donors’ skin.